PENCEGAHAN STUNTING MELALUI PENINGKATAN KAPASITAS KADER KESEHATAN DAN KUALITAS KESEHATAN LINGKUNGAN DI DESA PADAMUKTI - Humaedi, Sahadi; Nurwari, R. Nunung; Raharjo, Santoso Tri; Santoso, Meilanny Budiarti; A. Rachim, Hadiyanto (Universitas Padjadjaran, 2023)
Public health, environmental and education problems are not only the government's task in solving them but are the responsibility of all, including the academic community. Community Service Activities (PKM) are one of the many ways of dedicating themselves to academics to build society. In terms of public health problems in the Solokan Jeruk District, especially in Padamukti Village, it seems that this has not been optimal because: 1. Counseling and outreach regarding stunting prevention has not been carried out regularly, this is evidenced by the fact that there are several toddlers with indications of stunting. 2. There are still many early marriages, this is one of the causes of stunting because children born to underage mothers have a fairly high risk. 3. Cleaning facilities such as trash cans are still not available sufficiently so there is still a lot of garbage that has accumulated in one corner of the village, which causes environmental pollution. 4. The culture of community literacy is still very lacking so people are still consumed by incorrect information or hoaxes. Under these conditions, PKM is directed at counseling and seminars for the Padamukti village community, especially health cadres, namely: